The clinicopathological relevance of uniform CD56 expression in anaplastic large cell lymphoma: a retrospective analysis of 18 cases - Bao-Hua Yu; Yan Zhang; Tian Xue; Ruo-Hong Shui; Hong-Fen Lu; Xiao-Yan Zhou; Xiong-Zeng Zhu; Xiao-Qiu Li (BMC, 2021)
Abstract Background Anaplastic large cell lymphoma (ALCL) with uniform CD56 expression is a rare condition, that has been described in limited literature, and its clinicopathological features have not yet been well illustrated. The aim of our study was to fully investigate the clinical, histological, immunohistochemical and molecular features of CD56+ ALCL. Methods The clinical and histological characteristics of CD56+ ALCL cases were retrospectively evaluated. The immunohistochemical phenotype, status of Epstein-Barr virus (EBV) and T-cell receptor (TCR) gene rearrangement were examined. Overall survival was also analyzed. Results Eighteen (5.8%) cases with diffuse CD56 expression were identified out of 313 archived ALCL cases with CD56 test. CD56 expression was significantly higher in ALK+ systemic ALCLs (sALCLs) (13/64, 20.3%) than in ALK- sALCLs (3/101, 3.0%) (p < 0.001) as well as primary cutaneous ALCLs (2/148, 1.4%) (p < 0.001). Regarding the CD56+ ALK+ sALCLs, the median age was 20 years (range, 8-60 years) with a male-to-female ratio of 2.3:1, and these cases more frequently affected extranodal sites (11/38, 28.9%) rather than lymph nodes (2/26, 7.7%) (p = 0.038). Eleven (84.6%) cases presented with stage I-II diseases, which was significantly more than their CD56- ALK+ counterparts (45.5%) (p = 0.015). Histologically, 2 ALK+ cases were of small cell variant and all the others displayed characteristic morphology of classic ALCL. Regarding the immunophenotype, both CD30 and CD56 were diffusely positive in all cases. CD3, CD43, anaplastic lymphoma kinase-1 (ALK1), TIA-1, EMA expression was observed in 30.8% (4/13), 90.9% (10/11), 100% (13/13), 100% (9/9), and 80.0% (8/10) cases, respectively. EBV infection was consistently absent. Monoclonal TCR gene rearrangement was found in 100% (5/5) of investigated ALK+ cases. Chemotherapy with a CHOP regimen was most frequently employed. The 3-year overall survival (OS) rate for CD56+ ALK+ patients was 92.0%, compared with 73.0% for their CD56- counterparts, but there was no significant difference in OS between the two groups (p = 0.264). Conclusions Uniform CD56 expression is an unexpected condition in ALCL. Of ALK+ ALCLs, CD56 expression correlated with a high frequency of early stage and an extranodal predominance. It is of great importance to raise awareness of this condition and familiarity with its characteristic features to avoid diagnostic and therapeutic pitfalls. Further investigations are warranted for a better understanding of this unusual phenotype and the significance of CD56 expression in ALCL.